Analisis Faktor-Faktor yang Mempengaruhi Kompetensi Profesional Guru di Perguruan Tamansiswa Pematangsiantar - Yuswardi Yuswardi (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2021)
This study was to determine the factors that affect the professional competence of teachers at the Tamansiswa Pematangsiantar College. There is a simultaneous influence of work experience, education level, status, and the self-development of teachers on teacher competence. This study uses a quantitative approach to explore the factors that affect the professional competence of teachers at the Tamansiswa Pematangsiantar College. The dependent variable (dependent) is the professional competence of teachers. The total population is 129 teachers. The sample size is taken to be as many as 109 teachers. The statistical analysis used is multiple regression analysis and the residual test for the moderating variable.